An analysis of 1344 consecutive acute intoxication cases admitted to an academic emergency medicine department in Turkey - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (KARE PUBL, 2020)
OBJECTIVE: One of the major causes of emergency department (ED) visits is acute poisoning. Acute intoxications occur soon after either single or multiple exposures to toxic substances, and they started to be a more serious problem in developing countries. The objective of this study was to investigate the local patterns of acute intoxications, as well as clinical and sociodemographic characteristics of patients with acute poisoning, admitted to our hospital's ED. METHODS: This single-center, retrospective study was conducted using medical records of consecutive patients admitted to the ED between January 2016 and December 2017. RESULTS: A total of 1344 patients were included in the statistical analysis. Of these, 673 (50.1%) were female. Mean (+/- SD) age was 32.2 (+/- 12.0), ranging between 17 and 84 years. The highest number of poisoning cases was observed in summer, especially in July (10.0%) and August (11.8%), whereas lowest number of admissions related to poisoning occurred during winter in November (5.1%) and December (5.2%). Among admitted cases, many were suicide attempts (55.7%) followed by non-intentional (accidental) ingestion of non-pharmaceutical (n=553, 41.2%) and pharmaceutical agents (n=42, 3.1%). Single agents were the most common cause of acute intoxications (63.2%) rather than multidrug intoxications. Most frequently observed causes of poisonings were recreational substances (30.0%) and agents exposed by inhalation (13.2%). INR, lactate, and pH levels at admission were significant predictors of 7-day mortality without a significant paired difference between each other. The AUCs for each were 0.89 (SE 0.04; p<0.0001), 0.84 (SE 0.10; p=0.0007), and 0.79 (SE 0.11; p=0.0102), respectively. CONCLUSION: We conclude that recreational substances and medicinal drug intoxications were the leading cause of acute poisonings in our region, occurring mostly during the summer.
Keywords: Demographics; poisoning; toxicity; DEPARTMENT PATIENTS; PROGNOSTIC-FACTORS; ARTERIAL LACTATE; DRUG-OVERDOSE; POISONINGS; PROFILE; LEVEL